ANTITUMOR EFFECTS OF CHRYSANTHEMIN IN PC-3 HUMAN PROSTATE CANCER CELLS ARE MEDIATED VIA APOPTOSIS INDUCTION, CASPASE SIGNALLING PATHWAY AND LOSS OF MITOCHONDRIAL MEMBRANE POTENTIAL. - Sun, De-Kang; Wang, Lin; Zhang, Peng (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The main objective of the current research work was to investigate the antitumor and apoptotic effects of chrysanthemin in PC-3 human prostate cancer cells. Materials and Methods: MTT assay was used to evaluate the effects of chrysanthemin on cell viability whereas flow cytometry along with fluorescence microscopy were used to study apoptotic induction in these cells. Effects on caspase activation were detected through western blot assay. Results:Results showed that chrysanthemin inhibited cancer cell growth in PC-3 cancer cells in a time-dependent as well as concentration-dependent manner. Chrysanthemin-treated cells at 10, 50 and 150 μM doses led to 34.2%, 56.7% and 69.1% apoptosis in these cells respectively.The percentage of cells with depolarized mitochondria increased from 5.3% in untreated control cells to 27.2%, 57.6% and 86.9% in cells treated with 10, 50 and 150 μM dose of chrysanthemin respectively. Chrysanthemin also enhanced the activity of all three caspases viz., caspase-3, 8 and 9 in a dose-dependent fashion. Conclusions: The study concluded that chrysanthemin ledanticancer effects in PC-3 prostate cancer cells by inducing apoptosis, activating caspasesignaling pathway and loss of mitochondrial membrane potential.